Akt/Nox2/NF-κB signaling pathway is involved in Tat-induced HIV-1 long terminal repeat (LTR) transactivation - Zhang, Hong-Sheng; Sang, Wei-Wei; Ruan, Zheng; Wang, Yu-Ou (Archives of biochemistry and biophysics, 2011)
► Phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway is involved in Tat-induced NADPH oxidase stimulation. ► NF-κB nuclear translocation in Tat-treated MAGI cells is dependent on Nox2 activation. ► Akt/NADPH oxidase pathway is involved in Tat-induced LTR transactivation in MAGI cells. Human immunodeficiency virus (HIV) regulatory protein Tat has pro-oxidant property, which might contribute to Tat-induced long terminal repeat region (LTR) transactivation. However, the intracellular mechanisms whereby Tat triggers ROS production, and the relationship between Tat-induced ROS production and LTR transactivation, are still subject to debate. The present study was undertaken to evaluate the specific effects of Tat on nicotinamide adenine denucleotide phosphate (NADPH) oxidase in MAGI cells, and to determine the specific role of NADPH oxidase in Tat-induced LTR transactivation. Application of Tat to MAGI cells caused increases in ROS formation that were prevented by both pharmacologic NADPH oxidase inhibitors and by siRNA Nox2, but not by other inhibitors of pro-oxidant enzymes or siRNA Nox4. Furthermore, inhibition of NADPH oxidase by both pharmacologic NADPH oxidase inhibitors and by siRNA Nox2 attenuated Tat-induced p65 phosphorylation and IKK phosphorylation. Phosphatidylinositol 3-kinase/Akt signaling pathway was involved in Tat-induced NADPH oxidase stimulation. Finally, NADPH oxidase inhibitors or Nox2 siRNA, but not control siRNA, inhibited Tat-induced LTR transactivation. Tat-induced HIV-1 LTR transactivation was inhibited in wortmannin or LY294002 treated cells compared to control cells. Together, these data describe a specific and biologically significant signaling component of the MAGI cells response to Tat, and suggest the PI3K/Akt signaling pathway might originate in part with Tat-induced activation of NADPH oxidase and LTR transactivation.